Health promotion for dementia risk reduction in Indigenous populations of Canada, Aotearoa New Zealand, United States of America, and Australia: Scoping review protocol. - Kathryn Meldrum; Yvonne Hornby-Turner; Valda Wallace; Sarah G Russell; Rachel Quigley; Edward Strivens (PLoS ONE)
Health promotion programs and strategies have the potential to support people to live healthier lives. Dementia, a collective name for brain disorders that impact thinking and memory, affects over 55 million people worldwide. Currently, there is no cure for dementia, so prevention is critical. Health promotion has the potential to reduce dementia by targeting the twelve potentially modifiable risk factors. A project currently being undertaken by the research team aims to strengthen the quality of clinical care and health services that specifically address dementia risk for Australian Aboriginal and Torres Strait Islander peoples. One of the intended strategies supporting the project's aim is the need for appropriate and safe health promotion programs and resources that support dementia risk reduction. Consequently, the aim of this scoping review is to identify and determine the quality and appropriateness of existing health promotion programs and resources aimed at dementia risk reduction developed or modified for Indigenous populations of Canada, the USA, Aotearoa New Zealand, and Australia that could be incorporated into the broader project. The Joanna Briggs Institute method for scoping reviews will be used to identify programs and resources focussed on dementia risk reduction for Indigenous peoples. Searches will be limited to the English language and literature published since January 2010. Databases to be searched include: CINAHL, Medline, PsychInfo, PubMed, Scopus and Google. Data that answers the research questions will be extracted from the literature and recorded on a data charting form. A combination of quantitative and qualitative methods will be used to analyse the findings of the scoping review. Dissemination of the findings through continuing community engagement, conference presentations and publications will be led by Aboriginal and Torres Strait Islander members of the research team.